2016
DOI: 10.1155/2016/2161460
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 3D Nonstationary Channel Model Based on the von Mises-Fisher Scattering Distribution

Abstract: In the last decade, the nonstationary properties of channel models have attracted more and more attention for many scenarios, that is, vehicle-to-vehicle (V2V), mobile-to-mobile (M2M), and high-speed train (HST). However, little research has been done on the real-physical channel model. In this paper, we propose a generalized three-dimensional (3D) nonstationary channel model, in which the scatterers are assumed to be distributed around the transmitter (Tx) and receiver (Rx) on a two-sphere model. By employing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Nevertheless, the authors in [9,10] found that the WSS was only suitable for short distances between transmitters and receivers based on the measured data. Several GBSMs for nonstationary V2V channels are proposed in the literature [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Among them, 2D nonstationary V2V GBSMs with fixed clusters [11,12] or moving scatterers [13] were studied and the statistical properties, i.e., the temporal correlation function (TCF), spatial correlation function (SCF), and Doppler power spectrum density (DPSD), were also analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, the authors in [9,10] found that the WSS was only suitable for short distances between transmitters and receivers based on the measured data. Several GBSMs for nonstationary V2V channels are proposed in the literature [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Among them, 2D nonstationary V2V GBSMs with fixed clusters [11,12] or moving scatterers [13] were studied and the statistical properties, i.e., the temporal correlation function (TCF), spatial correlation function (SCF), and Doppler power spectrum density (DPSD), were also analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the authors in [7] have proved that the 3D channel model is more accurate than the 2D ones for evaluating the system performance. By extending the scatterers distributed on the surface of 3D regular shapes, i.e., a hemisphere [15], two cylinders [16,17], two spheres [18], an elliptic-cylinder [19], a rectangular tunnel [20], several 3D nonstationary V2V channel models were proposed recently. In [21], the authors proposed a 3D irregular-shaped GBSM for nonstationary V2V channels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The models in M2M communication environment can be traced back from two-dimensional (2D) [5][6][7] and three-dimensional (3D) [8][9][10][11] fixed scattering models to 2D [12][13][14][15][16][17] and 3D [18][19][20] moving scattering models. The M2M channel models with the assumption of stationary scatterers have been proposed in [5][6][7][8][9][10][11]. However, moving scatterers are unavoidable in M2M communications.…”
Section: Introductionmentioning
confidence: 99%